Strain-tuning of edge magnetism in zigzag graphene nanoribbons. (7th August 2017) - Yang, Guang; Li, Baoyue; Zhang, Wei; Ye, Miao; Ma, Tianxing
Abstract: Using the determinant quantum Monte-Carlo method, we elucidate the strain tuning of edge magnetism in zigzag graphene nanoribbons. Our intensive numerical results show that a relatively weak Coulomb interaction may induce a ferromagnetic-like behaviour with a proper strain, and the edge magnetism can be enhanced greatly as the strain along the zigzag edge increases, which provides another way to control graphene magnetism even at room temperature.